PHILOSOPHY OF THE HESICHASTIC PRACTICE ANTHROPOLOGY - Сідоріна, Є. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article is dedicated to the anthropological prospects of philosophic understanding of the Hesichastic practice, the article also reviews the discussions around the Imiaslavie movement, which where held by different religious schools of thought in the beginning of the 20th century and are as well of immediate interest nowadays.